Pendapatan Akuntansi Dan Harga Saham Terhadap Pertumbuhan Dalam Produk Domistik Bruto (PDB) - Ahmad Junidi; Slamet Haryono (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
The purpose of this research is to find out whether accounting income and stock prices can influence the movement of GDP growth. This study uses quantitative research methods, with up to 4 companies listed on the stock exchange using quarterly data from the period 2017-2019. The results showed that simultaneously variable stock price and accounting income can affect GDP growth. But partially. Whereas accounting income influences GDP growth positively and significantly.